Consumer Engagement in Health IT: Distinguishing Rhetoric from Reality - Gold, Marsha (EGEMS (Wash DC), 2015)
RATIONALE: Policymakers want health information technology (health IT) to support consumer engagement to help achieve national health goals. In this paper, we review the evidence to compare the rhetoric with the reality of current practice. CURRENT REALITY AND BARRIERS: Our environmental scan shows that consumer demand exists for electronic access to personal health information, but that technical and system or political barriers still limit the value of the available information and its potential benefits. CONCLUSIONS AND POLICY IMPLICATIONS: There is a gap between current reality and the goals for consumer engagement. Actions that may help bridge this gap include: (1) resolving technical barriers to health information exchange (HIE); (2) developing more consumer-centric design and functionality; (3) reinforcing incentives that attract provider support by showing that consumer engagement is in their interest; and (4) building a stronger empirical case to convince decision makers that consumer engagement will lead to better care, improved health outcomes, and lower costs.